Double port-a-cath implantation: initial experience in Brazil and technical note tips and tricks: a series report - Túlio Fabiano de Oliveira Leite (Journal of Medical Case Reports, 2024)
Abstract Background This study was designed to evaluate the clinical benefit of double-lumen port catheters in patients receiving chemotherapy and parenteral nutrition concurrently or in those with vascular access failure. The advantages, complications, indications and duration of use of double port-a-cath were considered. Methods Thirteen Brazilian patients received a double-lumen port catheter that was implanted under ultrasonographic and fluoroscopic guidance in the radiologic interventional suite. Results All double-lumen port systems were successfully implanted in all patients without immediate complications. The port-a-cath was removed in two patients due to infection of the reservoir. Three deaths occurred due to underlying disease with no correlation to the port-a-cath. No temporal interference between the administration of chemotherapy and parenteral nutrition was observed. Conclusion The double-door approach is a safe technique with low complication rates. Indications for use of the dual port are numerous and should be encouraged because of the considerable benefits for critically ill patients.